Nocturnal movements and habitat selection of mesopredators encountering bobwhite nests. (12th November 2014) - Cooper, Susan M.; Jhala, Shesh; Rollins, Dale; Feagin, Rusty A.
ABSTRACT: Northern bobwhites ( Colinus virginianus ) represent a valuable resource for upland game‐bird hunters and the rural economies they support; however, bobwhite populations are declining across the United States. As ground‐nesting birds, bobwhites are highly susceptible to mammalian predation during the breeding season. We placed global positioning collars on 6 coyotes ( Canis latrans ), 4 bobcats ( Lynx rufus ), and 11 raccoons ( Procyon lotor ) in Texas, USA, during the nesting season of bobwhites (April–August of 2009–2011) to assess their habitat selection and use, as well as determine the relative frequency with which they may encounter bobwhite nests. Overall, nightly encounter rate of predators with known bobwhite nest sites was low. Coyotes encountered nest sites 3 times more frequently than male raccoons and 7 times more frequently than bobcats. Female raccoons did not come within 50 m of any nest locations. The higher encounter rate of coyotes with bobwhite nest sites was associated with the similarity of habitat preference of coyotes and bobwhites for grasslands and grass–shrub habitats and the wide‐ranging nocturnal paths of coyotes. Bobcats and raccoons had shorter nightly paths and mainly used habitats providing a greater degree of cover than is typically suitable for nesting bobwhites. Male raccoons were more mobile than females and made greater use of the grass–shrub habitat, and thus were more likely to encounter quail nests. Despite having lower individual encounter rates with bobwhite nest sites than did coyotes, male raccoons remain important predators of quail nests because they have the behavioral ability to attain greater population densities than those of the more territorial coyotes and bobcats. © 2014 The Wildlife Society.